Strategic Interventions in Tackling Poor Performance of Service Departments: Study on Muhibbah Engineering (M) Bhd, Malaysia - Gopal, Sekar (Journal of Economics and Behavioral Studies, 2015)
This case study describes the problems faced by Muhibbah Engineering (M) Bhd group of companies (Malaysia) due to the poor performance of it’s service departments. This case was identified as a result of declining organizational performance of the company from the starting of year 2011 to early 2013. The main issues are declining profits (losses), delay in completing projects, customer complaints, skill depletion and poor organizational culture in the group besides other associated issues. The data related to the problems &issues are collected through personal discussions with the Project Directors of the company, company’s financial reports, financial research reports related to the company and through company’s website articles. The analysis is done on the inputs based on proven management concepts and theories such as leadership styles, organizational culture, span of control, performance management, human behavior and so on. The steps taken to mitigate the problems and the solutions are identifed through the changes made in the company through strategic interventions. The outcomes of each of the major interventions are recorded in this case study for the readers to understand and experiment them in similar and or different situations as the outcomes are positive and proven to be effective.